PEDAGOGICAL CONDITIONS OF EFFECTIVE PROFESSIONALLY ORIENTED COMMUNICATIVE TRAINING OF FUTURE OFFICERS OF CIVIL PROTECTION SERVICE - Yuliya Nenko (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the problem of formation of readiness of cadets of higher educational establishments of the SES of Ukraine to professionally oriented communicative activities. The author, based on scientific sources and personal experience teaching, discusses pedagogical conditions under which professionally oriented communicative training of future officers of civil protection in higher educational establishments of the SES of Ukraine will be more effective. These include: the formation of a cadet's value attitude to the future professionally oriented communicative activity; introduction of active and interactive teaching methods; optimization of the subject-subject interaction of participants in the educational process. Key words: pedagogical conditions; professionally oriented communicative training; cadet; future officer; higher educational establishment.